Saving enamel: safe removal of residual residues after detaching orthodontic brackets - Laís da Mata Almeida; Jieni Zhang Jing; Marcelo Souza Rodrigues; Leandro Augusto Hilgert; Rayssa Ferreira Zanatta (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT In conventional orthodontics, the adhesive fixation of brackets plays an essential role in the success of the treatment. However, the removal of these devices at the end of the treatment can pose risks of excessive wear to the external surface of the enamel, especially when rotary instruments are indiscriminately used to remove the resin composite employed in cementation. Given that enamel is an inorganic tissue with no regenerative capacity, it becomes imperative to adopt conservative techniques to minimize unnecessary wear. This text aimed to discuss more conservative approaches, exploring the use of multilayered burs instead of diamond tips, and associating them with polishing rubbers, magnification, and consideration of the fluorescence characteristics of adhesive materials. These practices are intended to minimize impact and preserve the integrity of the enamel. Reflecting on the indiscriminate use of diamond tips for enamel polishing emerges as essential in modern dental practice.